(untitled) (CAHIERS MAGELLANES-NS, 2024)
Fereydoon Moshiri and Malek osh-Sho'ara Bahar are two poets who, despite their disparate approaches to poetry, share a concern for protest and critical poems that address the social issues of society. The structure and manner of social criticism from the perspective of literature, particularly with a comparative approach in the works of these two poets, have not been studied to date; therefore, this descriptive-analytical study examines the similarities and differences of social criticism techniques regarding type, method, topic, audience of criticism, poetic style, and how to apply literary industries and the effect of social conditions on the critical view. According to the findings of this study, these two poets' perspectives on a variety of issues about social criticism are remarkably similar and are primarily influenced by their humanistic outlook. Bahar's criticisms are forthright, whereas Moshiri's criticisms are indirect. In addition, the most prevalent literary devices in the poems of the two poets are simile, metaphor, and irony, and the most prominent strategy for conveying the criticisms of both poets is imagery based on creating mental images with the aid of these arrays. The complaint is the most common way the two poets express social criticism in their poetry. However, the humorous expression as a defining characteristic of their social criticisms is significant in Bahar's poems but minor in Moshiri's. Style-wise, Bahar's phrases contain ancient or modern issues by approaching or straying from the linguistic level of speech in the manner of the literary return period. In contrast, Moshiri's critiques are met with an apparent consistency.